Shoe cleat position during cycling and its effect on subsequent running performance in triathletes - Viker, T.; Richardson, M. X. (Journal of Sports Sciences, 2013)
Research with cyclists suggests a decreased load on the lower limbs by placing the shoe cleat more posteriorly, which may benefit subsequent running in a triathlon. This study investigated the effect of shoe cleat position during cycling on subsequent running. Following bike-run training sessions with both aft and traditional cleat positions, 13 well-trained triathletes completed a 30min simulated draft-legal triathlon cycling leg, followed by a maximal 5 km run on two occasions, once with aft-placed and once with traditionally placed cleats. Oxygen consumption, breath frequency, heart rate, cadence and power output were measured during cycling, while heart rate, contact time, 200m lap time and total time were measured during running. Cardiovascular measures did not differ between aft and traditional cleat placement during the cycling protocol. The 5km run time was similar for aft and traditional cleat placement, at 1084 ±?80 s and 1072±64s, respectively, as was contact time during km 1 and 5, and heart rate and running speed for km 5 for the two cleat positions. Running speed during km 1 was 2.1%±1.8 faster (P?0.05) for the traditional cleat placement. There are no beneficial effects of an aft cleat position on subsequent running in a short distance triathlon.